Improving Vocabulary of The Eleventh Grade Students of SMA Negeri I Sa’dan Through Community Language Learning (Cll) - Nehru P. Pongsapan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2012)
The objective of the research is to find out the effective of Community Language Learning (CLL) in improving vocabulary for the eleventh grade students of SMA Negeri 1 Sa’dan. This research used quantitative research. It is to find out the mean score of pretest and posttest for the eleventh grade students of SMA Negeri 1 Sa’dan in improving vocabulary through Community Language Learning (CLL). The instrument of the research is written test. The population of this research is the eleventh grade students of SMA Negeri 1 Sa’dan academic year 2011/2012. The total of population is 54 students and taken 50 percents as sample in purposive sampling technique. The result of data analysis which is found out through written test that the mean score of pretest is 49.63 and the mean score of posttest is 63.51. It means that the mean score of posttest is higher 13. 88 points than pretest. It means that the implementation of Community Language Learning (CLL) is effective in teaching vocabulary for the eleventh grade students of SMA Negeri 1 Sa’dan. Based on the result of data analysis mentioned above, it can be concluded that The implementation of Community Language Learning (CLL) classroom approach for the eleventh grade student of SMA Negeri 1 Sa’dan is more effective .